Utilization of Aloe Vera Extract as A Natural Coagulant and its Effect on The Characteristics of IRR 118 Clone Rubber - Feerzet Achmad; Deviany Deviany; Fajri Aditya; Anggi Oktasari; Suhartono Suhartono; Suharto Suharto (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Rubber is one of the plantation products as a foreign exchange earner for the country. The process of processing rubber requires coagulants to accelerate coagulation. Aloe vera is a plant that contains compounds of organic acids, is expected to be able to accelerate the coagulation process. The purpose of this study was to determine the effect of the use of natural coagulants of aloe vera extract on the characteristics of IRR 118 clone rubber. The variations of the extracts used are natural coagulant extracts of aloe centrifugation and no centrifugation and the chemical coagulant format acid 3% as a comparison. Centrifugation of natural coagulant extract of aloe vera is carried out at a speed of 3000 rpm for 1 hour. The characterization of rubber analyzed was DRC (Dry Rubber Content), Po (Initial Plasticity), PRI (Plasticity Retention Index), ash content, evaporating substance content, mooney viscosity, dirt content, and nitrogen content. From the results of the study, it was obtained that the percentage of DRC, Po, PRI, and Mooney Viscosity was highest in AV natural coagulants without centrifugation, namely 28%, 36%, 80%, and 80%. The lowest percentage of ash, dirt and nitrogen content in natural coagulants of AV centrifugation was 0.38%, 0.014%, and 0.36%. Aloe vera natural coagulants without centrifugation and centrifuged ones can be used as coagulants for the latex coagulation process because they have met all the requirements of SNI SIR 20 and can be used as natural coagulants.